2012
DOI: 10.1016/j.jconrel.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release formulations of IL-2, TGF-β1 and rapamycin for the induction of regulatory T cells

Abstract: The absence of regulatory T cells (Treg) is a hallmark for a wide variety of disorders such as autoimmunity, dermatitis, periodontitis and even transplant rejection. A potential treatment option for these disorders is to increase local Treg numbers. Enhancing local numbers of Treg through in situ Treg expansion or induction could be a potential treatment option for these disorders. Current methods for in vivo Treg expansion rely on biologic therapies, which are not Treg-specific and are associated with many ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 45 publications
5
86
1
1
Order By: Relevance
“…Sustained release of both cytokines was comparable due to physiochemical similarities between both proteins. Both cytokines have individually been encapsulated in PLGA matrices previously [30,32], but they have not been co-encapsulated in the same particle. To verify preservation of each cytokine’s structure following PLGA encapsulation and particle synthesis, we assayed for bioactivity during particle-mediated release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained release of both cytokines was comparable due to physiochemical similarities between both proteins. Both cytokines have individually been encapsulated in PLGA matrices previously [30,32], but they have not been co-encapsulated in the same particle. To verify preservation of each cytokine’s structure following PLGA encapsulation and particle synthesis, we assayed for bioactivity during particle-mediated release.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we chose to use nanoparticles composed of poly(lactic-co-glycolic) acid (PLGA), which have been used extensively for the controlled delivery of various proteins to many cell types [2830]. Given the clear goal here, directed delivery of pleiotropic cytokines to CD4 + T cells, and its clinical implication for autoimmune treatment, we chose to use the simplest and most ubiquitous nanocarrier delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…A potential treatment option for these disorders revolves around increasing the number of Tregs in local sites (Jhunjhunwala et al, 2012;Gonzales et al, 2013). Current methods for in vivo expansion of Tregs depend on biological therapies, which are not specific for Tregs and are still associated with many adverse side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These formulations were also able to induce transcription factors FoxP3+ Tregs in human cells in vitro. The authors concluded that the combination of these microparticle formulations have the potential to be used for the in vivo induction of Tregs at local sites of rejected transplants or autoimmunity (Jhunjhunwala et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation